INVESTIGATING THE EFFECT OF PHOTOINITIATOR RATIO ON THE POLYMERIZATION SHRINKAGE IN DENTAL COMPOSITES BY TWO COMPARATIVE METHODS - Tekerek, Bilge Sema; Yucel, Sevil; Aydin, Ismail; Unal, Ahmet (YILDIZ TECHNICAL UNIV, 2015)
The prupose of this study was to investigate the effects of different ratios of photoinitiator and co-initiator on the polymerization shrinkage. Thus, dental composite materials were produced. Dental composites were composed of Bisphenol A-glycidyl methacrylate (BisGMA) and hydroxyethylmethacrylate (HEMA) as monomer matrix, camphoroquinone (CQ) as photoinitiator and 2-(dimethylamino) ethyl methacrylate (DMAM) as co-initiator. Silanized hydroxyapatite (HA) was used in inorganic phase as a reinforcing material. Polymerization shrinkage was measured by Archimedes principle and laser profilometer. Also, these methods were compared with each other in this study. Statistical analysis of the data was performed with ANOVA and Tukey's post hoc test. Results of shrinkage values obtained by two methods showed that ratios of photointiator and co-initiator were affected the polymerization and, hence shrinkage rate. Also, statistically differences between the values of Archimedes principle and laser profilometer.
Keywords: Dental composite; polymerizaiton shrinkage; photoinitiators; laser profilometer; Archimedes principle; LIGHT-CURED RESIN; MECHANICAL-PROPERTIES; PHYSICAL-PROPERTIES; CONTRACTION STRESS; CONVERSION; CAMPHORQUINONE; INITIATOR; KINETICS; SYSTEMS; AMINE; Engineering